Effect of scalp nerve block with ropivacaine on postoperative pain in pediatric patients undergoing craniotomy: A randomized controlled trial - Ning, Li; Jiang, Lai; Zhang, Qingqing; Luo, Mengqiang; Xu, Daojie; Peng, Yuanzhi (Frontiers in Medicine, 2022)
Background Scalp nerve block (SNB) is widely used for postoperative pain control, intraoperative hemodynamic control, and opioid-sparing in adult craniotomies. However, there are few studies of SNB in pediatric patients undergoing craniotomy. In the present study, we aimed to investigate the effect of SNB on postoperative pain, intraoperative hemodynamic stability, and narcotic consumption in pediatric craniotomy under general anesthesia. Methods This trial is a single-center, prospective, randomized, and double-blind study. A total of 50 children aged between 2 and 12 years who are undergoing elective brain tumor surgery will be randomly allocated in a 1:1 ratio to receive either 0.2% ropivacaine for SNB (group SNB, intervention group, n = 25) or the same volume of saline (group Ctrl, control group, n = 25). The primary outcome was to assess the score of postoperative pain intensity at time 1, 4, 8, 12, 24, and 48 h postoperatively using the FLACC score method. Secondary outcomes were to record intraoperative hemodynamic variables (MAP and HR) during skull-pin fixation, skin incision and end of skin closure, intraoperative total consumption of remifentanil and propofol, postoperative opioid consumption, and the incidence of postoperative nausea and vomiting. Results Fifty patients were analyzed (n = 25 in SNB group; n = 25 in control group). Compared to the control group, postoperative pain intensity was significantly relieved in the SNB group up to 8 h post-operatively. In addition, SNB provided good intraoperative hemodynamic stability, reduced intraoperative overall propofol and remifentanil consumption rate, and postoperative fentanyl consumption compared to the control group. However, the incidence of postoperative nausea and vomiting was not different between SNB and the control group. Conclusions In pediatric craniotomies, SNB with 0.2% ropivacaine provides adequate postoperative pain control and good intraoperative hemodynamic stability during noxious events compared to the control group. Clinical trial registration Chinese Clinical Trial Registry [No: ChiCTR2100050594], Prospective registration.